Evaluating the feasibility and utility of telephonic motivational interviewing in older adults - Nicholas R. Lamoureux; L. Alison Phillips; Kathryn J. DeShaw; Trina Radske-Suchan; Gregory J. Welk (Elsevier, 2024)
Older adults face unique barriers and challenges related to physical activity (PA) participation. Motivational interviewing (MI) is a commonly used health coaching strategy to support behavior change that holds potential for older adults. Previous research on MI strategies has focused primarily on face-to-face delivery, limiting insights regarding virtual programs. Objectives: The purpose of this study was to determine if MI could be delivered telephonically with high fidelity and high acceptability in older adult participants. The study is designed to inform future trials evaluating its effectiveness in supporting virtual PA programs. Methods: This study evaluated the feasibility and acceptability of telephonic MI among older adults that enrolled in an online version of the Walk with Ease program. Results: Of 39 participants referred, 29 enrolled and 27 provided feedback. Participants were highly accepting and adherent, with 74 % of patients attending at least five of six sessions, and 96 % of participants indicating satisfaction with the MI provided. Coaches improved program enjoyment by helping set effective goals and providing ongoing accountability. Conclusions: Evaluations documented adequate fidelity and high acceptability of telephonic delivery, and motivation results revealed large, significant increases in autonomous regulation (quality of motivation). Innovation: Telephonic MI using non-healthcare professional coaches is feasibly delivered with high fidelity, and is acceptable to older adult participants. The innovative delivery format offers novel opportunities supporting virtual and telehealth interventions to reduce chronic disease risk among older adults.